PENGEMBANGAN MODUL IPA BERBASIS ETNOSAINS PEMBUATAN IKAN ASAP PADA MATERI ZAT DAN PERUBAHANNYA - Syahputri, Cindy Eka; Hadi, Wiwin Puspita; Wulandari, Ana Yuniasti Retno; Yamin, Yamin; Hartiningsih, Try (Natural Science Education Research, 2025)
This study aims to determine the feasibility of the Ethnoscience-Based Science Module for Making Smoked Fish, the readability of the Ethnoscience-Based Science Module for Making Smoked Fish, and students' responses to the Ethnoscience-Based Science Module for Making Smoked Fish. The development model used is the ADDIE development model. The subjects of this study were grade VII students of SMP Negeri 15 Surabaya. The results of this study indicate that 1) the developed Science Module was declared "feasible" with the results of the material and media validity of 1.0 with the category of "high validity"; 2) the Science Module has a media readability level of 91.7% with the category of "high"; and 3) the Science Module has a student response level of 92% with the category of "very good". Therefore, learning media in the form of an ethnoscience-based Module can be used in learning activities.